2021
DOI: 10.3390/vaccines9101156
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Attitudes, Perceptions, and Side Effect Experiences in Malaysia: Do Age, Gender, and Vaccine Type Matter?

Abstract: This study aimed to investigate the attitudes, perceptions, and experiences of side effects with the COVID-19 vaccines in Malaysia among participants in the National Vaccination Program. A cross-sectional survey was conducted among a sample of vaccine-eligible and vaccinated individuals in Malaysia between May and July 2021. A total of 428 respondents completed the survey. A vast majority (98.6%) of the respondents had registered to be vaccinated. Twenty participants (4.7%) expressed concerns about either regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
65
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 39 publications
9
65
2
2
Order By: Relevance
“…This is not surprising, since it was well-known, even before the COVID-19 pandemic, that biological sex differences could influence the vaccine uptake, responses, and outcome [ 89 ]. Recent studies showed that the side effects of the Pfizer-BioNTech [ 87 , 90 , 91 ], AstraZeneca [ 90 , 91 , 92 ], Sinopharm [ 12 ], Sputnik V [ 11 ], SinoVac [ 91 , 93 ], Johnson & Johnson and Moderna [ 90 ] vaccines were significantly more frequent in females. With a view to reducing post-vaccination side effects in females and increasing immunogenicity in males, Ciarambino et al [ 94 ] recommended that the vaccine development should be sex-specific, and that sex-related variables should be examined in pre-clinical and clinical vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising, since it was well-known, even before the COVID-19 pandemic, that biological sex differences could influence the vaccine uptake, responses, and outcome [ 89 ]. Recent studies showed that the side effects of the Pfizer-BioNTech [ 87 , 90 , 91 ], AstraZeneca [ 90 , 91 , 92 ], Sinopharm [ 12 ], Sputnik V [ 11 ], SinoVac [ 91 , 93 ], Johnson & Johnson and Moderna [ 90 ] vaccines were significantly more frequent in females. With a view to reducing post-vaccination side effects in females and increasing immunogenicity in males, Ciarambino et al [ 94 ] recommended that the vaccine development should be sex-specific, and that sex-related variables should be examined in pre-clinical and clinical vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparison of age groups showed that participants aged 20 to 39 years were more likely to experience almost the majority of post-vaccination side effects, and they constituted the largest proportion of participants who suffered from severe side effects. Studies on different populations also showed that the side effects of different COVID-19 vaccines were significantly more frequent in younger individuals compared to in the elderly [ 11 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review shows the average of local side effects was Injection site pain 77.34%, considered the most often occurring local adverse effect, followed by local swelling 33.57%. According to research published in 2021 by Elnaem et al, pain at the injection site (61.1%) and fatigue (48.8 %) were the most frequently reported adverse effects among individuals who got Pfizer vaccination [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Abu-Hammad et al demonstrated that adverse effects were more prevalent after the second dosage [ 48 ]. According to Elnaem et al, around 40% of adverse effects occurred more often with the second dosage, especially in those who got the Pfizer-BioNTech vaccination vs. those who received the Sinovac or AstraZeneca vaccine [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…The reported post-vaccination side effects were mild and no need to hospitalization(CDC, 2021). So the study will be helpful to reduce vaccine hesitancy among people Elnaem et al (2021). have investigated the attitudes, perceptions, and experiences of the COVID-19 vaccine side effects in Malaysia through a cross-sectional survey conducted between May and July 2021.…”
mentioning
confidence: 99%